2019
DOI: 10.1097/md.0000000000015870
|View full text |Cite
|
Sign up to set email alerts
|

Torsional and burst mode phacoemulsification for patients with hard nuclear cataract

Abstract: This article aims to evaluate the outcomes of torsional and burst mode phacoemulsification in hard nuclear cataracts. Eighty eyes with grade IV or V nuclear opalescence were treated with phacoemulsification and intraocular lens implantation using conventional mode (Group A, n = 40) or torsional and burst mode phacoemulsification (Group B, n = 40). For good visualization of anterior capsule, trypan blue was injected to the anterior chamber before continuous circular capsulorhexis. The mean cumulative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…4,6 Yang et al compared the conventional continuous mode of phaco with torsional and burst combination mode. 10 This study showed that Burst mode reduced the cumulative dissipation of energy during phacoemulsification of hard cataract. Besides, the torsional mode decreased the ultrasonic energy and saved the phaco power.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…4,6 Yang et al compared the conventional continuous mode of phaco with torsional and burst combination mode. 10 This study showed that Burst mode reduced the cumulative dissipation of energy during phacoemulsification of hard cataract. Besides, the torsional mode decreased the ultrasonic energy and saved the phaco power.…”
Section: Discussionmentioning
confidence: 80%
“…Technology advances and the development of various techniques in phaco procedure provide a safe way to operate different types of cataracts with different nuclear hardness. 10 The main goal of these developments is to reduce the ultrasound power delivered in the anterior chamber, which results in protection of endothelial cells and better visual acuity afterward. Phaco power is determined by a frequency which is the speed of needle movement (cycle per second) and stroke length.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Various modalities used to minimize ultrasound energy and reduce damage to surrounding ocular structures during phacoemulsification include direct phaco chop, crater and chop, power modulations in the form of torsional, variable pulse and burst modes, and phaco tips with decreased amplitude near the incision. [4][5][6][7][8][9][10][11][12][13] In order to minimize endothelial cell loss associated with mechanical trauma, maneuvers such as endocapsular or deeper plane phacoemulsification of totally separated small nuclear fragments, hypothermic perfusion, employment of fluidics to provide a stable anterior chamber, anterior chamber maintainer, replenishing anterior chamber with ophthalmic viscosurgical device (OVD), and use of femtosecond laser or manual prechopping techniques have been described. 2,4,11,[14][15][16][17] However, these modalities do not ensure the prevention of hard nuclear fragments from coming into physical contact with the corneal endothelium during surgery, thereby causing focal endothelial cell loss and precipitating corneal edema in the early postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…The latest, safest and most popular cataract extraction technique performed worldwide is phacoemulsification with posterior chamber intraocular lens implantation [ 1 ]. It involves minimal ultrasonic power and surgical tissue manipulation, lesser postoperative inflammation and early visual restoration [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latest, safest and most popular cataract extraction technique performed worldwide is phacoemulsification with posterior chamber intraocular lens implantation [ 1 ]. It involves minimal ultrasonic power and surgical tissue manipulation, lesser postoperative inflammation and early visual restoration [ 1 ]. However, the mechanical and ultrasonic energy induces breakdown of the ocular blood-aqueous barrier and thereby can potentially cause inflammation which manifests as conjunctival hyperemia, anterior chamber (AC) reaction, raised intraocular pressure (IOP) and cystoid macular oedema (CME) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%